Oxazoles for click chemistry II: synthesis of extended heterocyclic scaffolds. Issue 23 (3rd June 2015) - Patil, Pravin C.; Luzzio, Frederick A.; Demuth, Donald R.
Graphical abstract: Abstract: New routes to 2, 4, 5-trisubstituted oxazoles were established whereby the substitution pattern was established by the structure of the starting nonsymmetrical acyloins. 2-Chloromethyl-4, 5-disubstituted oxazoles were prepared by refinements of an earlier described process whereby chloroacetyl esters of symmetrical and nonsymmetrical acyloins were cyclized using an ammonium acetate/acetic acid protocol. After substitution is effected, the azide moiety is then installed by substitution under mild conditions. While dibrominated and iodinated phenyloxazoles are required for further synthetic elaboration, the cyclization reaction was found to be very sensitive to the relative positions of the halogens in the starting materials.